Growth and yield performances, pathogenicity, heat tolerance, antioxidant activity, and pungency level of anthracnose resistant and heat tolerant inbreed lines and their F1 hybrids of chili (Capsicum annuum L.) - Chowdhury, Mst. Farhana Nazneen; Rafii, Mohd Y.; Ismail, Siti Izera; Ramlee, Shairul Izan; Hosen, Monir; Karim, K. M. Rezaul; Ikbal, Mohammad Ferdous; Halidu, Jamilu; Sahmat, Siti Sahmsiah (Elsevier, 2022)
Chili pepper (Capsicum annuum L.) cultivation is hampered by biotic and abiotic stressors, with poor performance caused by high temperatures exceeding 42 °C and anthracnose infestation. Chemical constituents such as antioxidants, phenols, capsaicin, and dihydrocapsaicin have a relationship with biotic and abiotic tolerance or resistance. Experiment was conducted with anthracnose resistant (CP-36, DP-37, DP-57, AP-25 and BP-23), heat tolerant inbreed lines (Putra chili 1, Putra chili 4, Putra chili 7, Putra chili 9 and Putra chili 10) and their hybrids to find anthracnose-resistant, heat-tolerant chili genotypes with high yield and pungency levels. For this purposes, pathogens were injected into both unripe and ripe chili fruits to determine their pathogenicity. On the other hand, four-week-old seedling was raised for a heat tolerance test to determine the percentage of partial damage (%) and thermo-stability index of the cell membrane (%). The research also included morphological, yield and yield contributing, physiological, and biochemical assessment in order to identify superior chili hybrids. All growth, yield, and physiological traits showed excellent genetic progress and heritability, but correlation analysis showed a highly significant positive link between yield per plant, plant height, the total number of branches, and the number of fruits per plant. Lesion area of unripe fruits were varied from 0.00 (cm2) to 0.24 (cm2) and 0.00 (cm2) to 0.18 (cm2) for the pathogen, UPMC1191 (Colletotrichum fructicola) and UPMC1192 (Colletotrichum sojae), respectively and also indicated that differential resistant to anthracnose pathogen. In a heat tolerance test, all of the hybrids with the improved heat tolerant line performed better in terms of cell membrane thermo-stability, partial damage at various temperature gradients, and canopy temperature depression. In terms of biochemical state, DP-37 × Putra chili 7; AP-25 × Putra chili 10 had a moderate level of pungency, while some other parents and hybrids had mild level of pungency. After screening with Colletotrichum pathogen, heat tolerance test, biochemical constitute and yield performance, following hybrids would be better for commercial production to meet up the demand such as CP-36 × Putra chili 1; CP-36 × Putra chili 7; CP-36 × Putra chili 9; DP-37 × Putra chili 1; DP-37 × Putra chili 10; DP-37 × Putra chili 4; DP-37 × Putra chili 7; DP-37× Putra chili 9; DP-57 × Putra chili 7; DP-57 × Putra chili 9; DP-57 × Putra chili 10; AP-25 × Putra chili 9; AP-25 × Putra chili 4; BP-23 × Putra chili 7; BP-23 × Putra chili 9; BP-23 × Putra chili 1 and would be use in future chili breeding program.